STRATEGIC ESG DISPARITY AND BANK PERFORMANCE: EVIDENCE FROM BANKS FINANCING SMEs IN EMERGING ECONOMIES POST COVID-19 - Ali , Nurul Nabilah (International Journal of Small and Medium Enterprises, 2024)
This study examines the strategic disparity in Environmental, Social, and Governance (ESG) practices and their effects on bank performance in emerging economies during the post-COVID-19 period. Banks particularly those financing SMEs faced increased institutional pressure following the pandemic to integrate ESG into their operational strategies. However, the allocation of resources across the ESG pillars often varied significantly. This disparity, defined as the uneven commitment to the E, S, and G pillars, is considered a strategic response to institutional and financial constraints. The objective of this study is to examine, specifically in terms of return on assets (ROA) and return on equity (ROE). Employing a panel dataset of 398 publicly listed banks across 35 emerging countries from 2020 to 2023, many of which provide financing to SMEs, the study uses fixed-effects regression and multiple robustness checks to explore this relationship. The results suggest that banks with greater ESG disparities may yield higher returns, indicating that selective investment in specific ESG pillars may lead to greater returns. Meanwhile, the positive impact is less pronounced in countries with high climate risk. Subsample analyses further indicate that banks subject to mandatory ESG disclosures and more substantial commitments to environmental and social components outperform those that are not. The governance pillar, in contrast, has a relatively minor impact on ESG disparity and bank performance. These findings emphasize that ESG disparity is a deliberate strategy banks employ to optimize resource allocation and enhance performance outcomes in response to external.JEL Classification Codes: M14, G21, O16.